Detection of actionable mutations in archived cytological bile specimens. (21st June 2021) - Ohyama, Hiroshi; Hirotsu, Yosuke; Amemiya, Kenji; Oyama, Toshio; Iimuro, Yuji; Kojima, Yuichiro; Mikata, Rintaro; Mochizuki, Hitoshi; Kato, Naoya; Omata, Masao
Abstract: Background/Purpose: There are limitations in obtaining sufficient pancreaticobiliary tumor tissue for genomic profiling of tumors. Herein, we investigated whether archived cytological specimen (ACS) is suitable for genomic profiling to identify oncogenic and drug‐matched mutations. Methods: We constructed a pancreaticobiliary cancer panel for targeted sequencing covering 60 significantly mutated genes (280 220 bp). Eighty DNA samples (19 formalin‐fixed paraffin‐embedded [FFPE] tissues and 61 ACS) from 44 patients with pancreaticobiliary disease were analyzed. We compared genomic profiles of 19 FFPE and 29 ACS from 19 patients with malignancies ( Validation Cohort ). We tested 32 ACS from 25 patients (15 malignant and 10 benign) for the ability to discriminate between malignant and benign disorders ( Testing Cohort ). We explored whether actionable and drug‐matched mutations ( Validation and Testing Cohorts ) could be identified from ACS. Results: Oncogenic mutations observed in ACS were identical to those identified in FFPE specimens (76% consistency). Genomic profiling using only ACS discriminated between malignant and benign disorders with 93% accuracy, 91% sensitivity, and 100% specificity. Actionable and drug‐matched mutations were identified in 74% and 32% of ACS, respectively, and in 79% and 21% in FFPE samples, respectively. Conclusion: Archived cytological specimen may be used to discriminate malignancy and to detect drug‐matched mutations in patients with advanced pancreaticobiliary cancer. Abstract : Highlight There are limitations in obtaining sufficient pancreaticobiliary tumor tissue for genomic profiling. Ohyama and colleagues found that archived cytological specimens were comparable to formalin‐fixed paraffin‐embedded tissues in their ability to discriminate malignancies and detect drug‐matched mutations in advanced pancreaticobiliary cancer, and may help expand the patient population benefiting from targeted drugs.